H5P-Based Interactive Video Learning Media to Enhance Elementary Students’ Critical Thinking Skills - Kadek Ananda Pratiwi; I Made Citra Wibawa; Kade Sathya Gita Rismawan (Universitas Pendidikan Ganesha, 2025)
Critical thinking skills are essential 21st-century competencies that every individual needs to possess. However, the level of students’ critical thinking skills in Indonesia is still relatively low. This study aims to design, validate, and examine the practicality of interactive video-based learning media developed using the H5P website, as well as to test the effectiveness of this media in improving the critical thinking skills of fifth-grade elementary school students. The development model employed in this study was the ADDIE model. Data were collected through questionnaires and tests, while data analysis was conducted using qualitative and quantitative techniques. The research subjects consisted of two media and content experts, two teacher practitioners, and 24 fifth-grade students. The results indicate that the H5P-based interactive video learning media achieved a very high level of validity, with validity scores of 0.97 from media experts and 0.92 from content experts. The practicality of the media was also categorized as very high, with average scores of 3.85 from teachers and 4.00 from students. Furthermore, the effectiveness test results demonstrate that the H5P-based interactive video learning media is effective in enhancing students’ critical thinking skills. Therefore, it can be concluded that the H5P-based interactive video learning media is valid, practical, and effective in improving students’ critical thinking skills, enriching the variety of learning media, and creating more optimal learning experiences.